Deep Learning in Indonesian Education: Conceptual Foundations, Policy Frameworks, and Implementation - T. Wisnu Warnia WR; Dini Fitriani; Fadilla Oktaviana (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2026)
This study examines deep learning as an educational approach within the Indonesian education system by exploring its conceptual foundations, policy frameworks, and practical implementation. The background of the study arises from ongoing challenges in Indonesian classrooms, where teacher-centered instruction and surface learning practices remain dominant, limiting students’ critical thinking, engagement, and real-world application of knowledge. The study aims to analyze how deep learning, characterized by mindful, meaningful, and joyful learning, is conceptualized in educational theory, reflected in national education policies, and implemented in classroom practices. Using a qualitative literature review method, data were collected from peer-reviewed national and international journal articles, academic books, and research reports related to deep learning in education. The data were analyzed through thematic synthesis to identify patterns concerning implementation strategies, learning outcomes, and implementation challenges. The findings indicate that deep learning contributes positively to students’ cognitive development, motivation, engagement, and 21st-century skills, particularly critical thinking, collaboration, and creativity. However, its implementation in Indonesia faces several obstacles, including limited teacher competence, inadequate assessment systems, insufficient contextual learning materials, and unequal technological infrastructure. The study concludes that successful deep learning implementation requires integrated policy support, continuous teacher professional development, contextualized curriculum design, and equitable access to learning resources. These findings provide practical implications for educators, curriculum developers, and policymakers in strengthening sustainable and humanistic education in Indonesia.